2021
DOI: 10.1039/d1ta01007g
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight-activated phase change materials for controlled heat storage and triggered release

Abstract: We report the design of photo-responsive organic phase change materials that can absorb filtered solar radiation to store both latent heat and photon energy via simultaneous phase transition and photo-isomerization....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(118 citation statements)
references
References 44 publications
4
105
1
Order By: Relevance
“…Similar studies have captured thermal energy in a series of arylazopyrazoles, which can almost cover all the visible light area from the solar irradiation spectrum and release the stored energy by optically triggered crystallization at various temperature ranges (Figure 4B). 55,62,82,83,84 This concept has also been applied to develop AZO-based dendrimers as advanced soft matter systems, with some interesting switchable adhesive properties in addition to solar energy storage purpose. 85 Until now, we have mostly discussed systems where substituents have been used to improve solar spectrum match, solubility, and thermal stability.…”
Section: Ll Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies have captured thermal energy in a series of arylazopyrazoles, which can almost cover all the visible light area from the solar irradiation spectrum and release the stored energy by optically triggered crystallization at various temperature ranges (Figure 4B). 55,62,82,83,84 This concept has also been applied to develop AZO-based dendrimers as advanced soft matter systems, with some interesting switchable adhesive properties in addition to solar energy storage purpose. 85 Until now, we have mostly discussed systems where substituents have been used to improve solar spectrum match, solubility, and thermal stability.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…129 In general, AZO compounds show excellent cyclability and several studies have reported more than 200 energy storage cycles with little or no degradation. 62,82,130 FROM LAB DEMONSTRATION TO DEVICE…”
Section: Cycling Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, many applications benefit from switching with lowenergy and low-intensity light as well as from high thermal stability of the metastable cis-isomer. These attributes are crucial for switches used in living systems 19 or memories 20 and often times advantageous for applications in solar thermal fuel systems 21,22 and soft-robotic materials [23][24][25] as well: high-energy irradiation generally has a degrading effect on the switch and its surroundings 26,27 and, on the other hand, constant illumination is not always possible.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the total thermal energy storage density of cis-B7-S5 was 0.25 MJ kg -1 (79 kJ mol -1 ). According to Φtrans→cis and ΔHiso, the solar efficiency η was estimated to be 1.3% (see Section 5 in SI), which was one of the highest values reported for azobased molecular solar thermal batteries (0.2-1.3%) 27,32 . Owing to the fast transition of cis-liquid to trans-crystal triggered by green light, the energy of ΔHiso and ΔHcry were released on demand and rapidly.…”
Section: Resultsmentioning
confidence: 93%